A performance-based method for seismic evaluation of masonry walls strengthened with RC layers - Ghiassi, Bahman (2012)
A conventional method for seismic strengthening of masonry walls is externally application of reinforced concrete layer (shotcrete). However, due to the lack of analytical and experimental information on the behavior of strengthened walls, the design procedures are usually followed based on the empirical relations. Using these design procedures have resulted in massive strengthening details in retrofitting projects. This paper presents a computational framework for nonlinear analysis of strengthened masonry walls and its versatility has been verified by comparing the numerical and experimental results. Based on the developed numerical model and available experimental information, design relations and failure modes are proposed for strengthened walls in accordance with the ASCE 41 standard. Finally, a sample masonry structure has been strengthened using the proposed and available conventional methods. It has been shown that using the proposed method results in lower strengthening details and appropriate (ductile) failure modes